2019
DOI: 10.3390/plants8100398
|View full text |Cite
|
Sign up to set email alerts
|

Segregation Distortion Observed in the Progeny of Crosses Between Oryza sativa and O. meridionalis Caused by Abortion During Seed Development

Abstract: Wild rice relatives having the same AA genome as domesticated rice (Oryza sativa) comprise the primary gene pool for rice genetic improvement. Among them, O. meridionalis and O. rufipogon are found in the northern part of Australia. Three Australian wild rice strains, Jpn1 (O. rufipogon), Jpn2, and W1297 (O. meridionalis), and one cultivated rice cultivar Taichung 65 (T65) were used in this study. A recurrent backcrossing strategy was adopted to produce chromosomal segment substitution lines (CSSLs) carrying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…For preliminary linkage analysis using the cross between Koshihikari and XM6, we used 108 published SSR and Indel markers developed by Busungu et al (2016) , Chen et al (1997) , Ichitani et al (2011) , IRGSP (2005) , McCouch et al (2002) , Monna et al (2006) , Panaud et al (1996) , Shen et al (2004) , Temnykh et al (2000) , Toyomoto et al (2019) , and Rice Genome Research Program ( ) ( Table 2 , Supplemental Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…For preliminary linkage analysis using the cross between Koshihikari and XM6, we used 108 published SSR and Indel markers developed by Busungu et al (2016) , Chen et al (1997) , Ichitani et al (2011) , IRGSP (2005) , McCouch et al (2002) , Monna et al (2006) , Panaud et al (1996) , Shen et al (2004) , Temnykh et al (2000) , Toyomoto et al (2019) , and Rice Genome Research Program ( ) ( Table 2 , Supplemental Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Li et al [ 23 ] identified five hybrid pollen sterility genes, all of which follow the pollen-killer model [ 15 , 16 ]. No genes conferring hybrid seed sterility have been reported in the cross between O. meridionalis and the other AA genome species before our recent study [ 24 ], in which we reported seed abortion after fertilization in the progeny from the cross between O. sativa and O. meridionalis was controlled by a SEED DEVELOPMENT 1 ( SDV1 ) gene and a SEED DEVELOPMENT 2 ( SDV2 ) gene. This gene model is not an egg-killer model but a duplication and loss of a functional gene for seed development鈥攁 new finding in rice genetics.…”
Section: Introductionmentioning
confidence: 72%
“…Several markers deviated from expected Mendelian ratios were observed (Figure S1). Segregation distortion might be caused by several reproductive isolation mechanisms [56,57]. Therefore, some reproductive isolation mechanisms might exist between N. debneyi and N. fragrans.…”
Section: Discussionmentioning
confidence: 99%